Evaluation of the Antibacterial Activity of Methanolic Extracts of Hemigraphis Alternata and Ocimum Sanctum Against Wound-Infecting Bacteria: A Preliminary Investigation - Parvathy Prasad (International Journal of Pharmaceutical & Biological Archive, 2025)
The antibacterial activities of Hemigraphis alternata and Ocimum sanctum methanolic extracts were evaluated against wound pathogens Pseudomonas aeruginosa and Staphylococcus aureus. The agar well diffusion method was used as a qualitative assessment to observe the antibacterial effect of the methanolic extract of H. alternata and O. sanctum against wound-infecting bacteria. H. alternata exhibited a significant zone of inhibition at 500 microgram per milliliter against P. aeruginosa (16 mm) and S. aureus (14 mm), with a minimum inhibitory concentration (MIC) of 100 microgram per milliliter. Conversely, O. sanctum showed a zone of inhibition of 12 mm against P. aeruginosa at 1000 microgram per milliliter but exhibited no activity against S. aureus, with an MIC of 1000 microgram per milliliter. These findings suggest that methanolic extracts of H. alternata and O. sanctum have potential as components in wound healing formulations to enhance antibacterial efficacy.